Landslide inventory, susceptibility mapping and recommendation of the mitigation measures in Nuwakot District (Journal of Nepal Geological Society, 2017)
Nepal earthquake of 25th April 2015 and subsequent big aftershocks impacted people, land, and water resources significantly. Following the devastating earthquake, land and water management has become one of the primary focuses of the Government of Nepal as these resources are foundations of people’s livelihood and prosperity. The weakened, cracked, and destabilized slopes and surfaces due to the earthquake become even more susceptible to landslides that can be aggravated due to rainfall and inappropriate anthropogenic activities. Due to the devastating earthquake, 31 districts of Nepal out of 75 were affected with 14 being severely affected resulted huge loss of human life, property, and ecosystem services. These 14 districts were categorized as severely hit and crisis hit districts by the post disaster need assessment (PDNA) carried out by Government of Nepal. Nuwakot district is one of the severely hit districts. In order to reduce vulnerability and/or threat of potential landslide disasters and protect local people, infrastructures, land and water resources from potential landslide disaster, identification of the most susceptible slopes as well as treatment and mitigation of the most critical landslides deemed essential. This study has identified the landslides and its impact within different VDCs of Nuwakot district. The mitigation measures for the urgent and treatable landslides are purposed with the tentative estimation of the cost and prioritized them based on the social, environmental and economic criteria. Out of 542 landslides identified, 105 landslides were studied in detail based on social and physical risk. The study showed that the northern part of the district is more susceptible to landslides and consequent disaster. VDCs like Bhalche, Ghyangphedi, Salme, Urleni, Kimlang, Lachyang, Ralukadevi are more susceptible to the landslides in Nuwakot district.